2015
DOI: 10.3390/jmse3030674
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Predictions of Wave Runup, Extreme Water Levels, and Medium-Term Dune Erosion during Storm Conditions

Abstract: Monitoring of dune erosion and accretion on the high-energy macrotidal Vougot beach in North Brittany (France) over the past decade (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014) has revealed significant morphological changes. Dune toe erosion/accretion records have been compared with extreme water level measurements, defined as the sum of (i) astronomic tide; (ii) storm surge; and (iii) vertical wave runup. Runup parameterization was conducted using swash limits, beach profiles, and hydrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 46 publications
1
46
0
Order By: Relevance
“…Zeigler et al, 1959;Lee et al, 1998;Houser et al, 2008;Castelle et al, 2015;Suanez et al, 2015) to sandy beaches (Wright and Short, 1984;Sexton and Hayes, 1991;Morton, 2002;Priestas and Fagherazzi, 2010) and dunes (Saunders andDavidson-Arnott, 1990, Hesp, 2002;Psuty et al, 2005;McLean and Shen, 2006;Houser, 2012;Plant and Stockdon, 2012;Lentz et al, 2013;Houser et al, 2015;Weymer et al, 2013;Wilson et al, 2015). These studies assess change using a variety of beach metrics including island volume, shoreline and dune position, and profile topography from consecutive elevation surveys (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeigler et al, 1959;Lee et al, 1998;Houser et al, 2008;Castelle et al, 2015;Suanez et al, 2015) to sandy beaches (Wright and Short, 1984;Sexton and Hayes, 1991;Morton, 2002;Priestas and Fagherazzi, 2010) and dunes (Saunders andDavidson-Arnott, 1990, Hesp, 2002;Psuty et al, 2005;McLean and Shen, 2006;Houser, 2012;Plant and Stockdon, 2012;Lentz et al, 2013;Houser et al, 2015;Weymer et al, 2013;Wilson et al, 2015). These studies assess change using a variety of beach metrics including island volume, shoreline and dune position, and profile topography from consecutive elevation surveys (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…recovery with respect to what reference point). Furthermore, where storm-driven change is typically determined by the hydrodynamics of the event including waves, tides, and storm surge (Lee et al, 1998;Stockdon et al, 2007;Sallenger, 2000;Suanez et al, 2015), recovery can be affected by both hydrodynamic conditions (e.g. Scott et al, 2016) and aeolian sediment transport (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On a macrotidal environment, Suanez et al (2015) obtained good empirical runup relationships between observed and predicted runup using the slope of the active section of the beach. Their experiment was conducted during 5 years to enhance the range of conditions (wave heights, periods and beach slopes) under which the formula was parameterized with a slope value varying depending on hydrodynamic and tidal conditions, especially the water level.…”
Section: Introductionmentioning
confidence: 84%
“…Such basic formulae require, however, a study of the beach morphology, since in natural settings, the beach slope is not easy to identify (Holman and Sallenger 1985;Nielsen and Hanslow 1991;Cariolet and Suanez 2013;Suanez et al 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation